Application of Active Learning Methods in Developing Early Children’s Confidence Capabilities - Septimia Puspa Hastria Sayu Wiwit (Early Childhood Education & Parenting, 2024)
Action learning or active learning is a model or strategy involving children directly in the learning process. Not all children have the confidence to express their will and potential in school because the situation and environment are different from their home environment such as new teachers, new friends and a new atmosphere. The different abilities and potentials of children, spur teachers to always encourage and motivate them so that they dare to express and explore. Without the self-confidence built by the teacher in the learning process, the potential they develop is less optimal. Therefore, the application of the active learning method is very supportive in developing children's self-confidence. This research uses a qualitative type of research (constructivist) using the answer and question method, assigning tasks and involving children directly in child-centred activities or learning (student centre). This study found that children who were directly involved in learning were more confident, courageous, able to interact with friends and teachers, communicative, imaginative, creative and innovative because all of their five senses are used.